A cognition-driven framework for the evaluation of startups in the digital economy - Simões, J.; Ferreira, F.; Peris-Ortiz, M.; Ferreira, J. (Management Decision, 2020)
Purpose – Capital restrictions normally exist in the creation of a startup, requiring investors to analyze funding alternatives in a highly competitive climate. Although different types of incentives to support startups exist, these incentives are only available to those companies that fulfill the requirements of the funding program to which they have applied. Due to social and economic changes introduced by the digital economy, however, existing mechanisms for assessing the potential growth of startups are scarce, outdated or simply incomplete, distorting the results of such evaluations. Design/methodology/approach – Evaluating business opportunities and how to exploit them are critical activities to an entrepreneur. This study sought to address this issue through the combined use of cognitive mapping and the Decision EXpert (DEX) technique. Assuming a constructivist stance, the study brought together a panel of experienced entrepreneurs and business investors to identify and articulate the criteria to be considered in the evaluation and classification of startups. Findings – The evaluation system created in this study was tested, and the results were validated by the expert panel on a collective basis, demonstrating that the dual methodology used can increase our understanding of the decision problem at hand and lead to more informed and potentially better evaluations of the potential growth of startups. Originality/value – The authors know of no prior work reporting the integrated use of cognitive mapping and DEX in this study context.